Price escalation for the unit rate of light weight concrete due to unusual increase of price of cement - M/S Green Concrete (Brac University, 2023)
This variation order has been made between Brac University and M/S Green Concrete for price escalation for the unit rate of light weight concrete due to unusaual increase of price of cement of Brac University new campus project.